Digestion, absorption, and transport properties of soy-fermented douchi hypoglycemic peptides VY and SFLLR under simulated gastrointestinal digestion and Caco-2 cell monolayers. (February 2023) - Yu, Songfeng; Wang, Wenjun; Bu, Tingting; Zhao, Runan; Niu, Ruihao; Liu, Ling; Li, Jiaheng; Wu, Jianping; Liu, Donghong
Graphical abstract: Highlights: Peptide VY was resistant, whereas SFLLR was susceptible to simulated gastrointestinal digestion. Two new hypoglycemic peptides (SFLL and SFL) were formed from digestion of SFLLR. Transport of peptide VY and SFL was mediated by both paracellular diffusion and PepT1 route. Transport of SFLLR and SFLL was paracellular diffusion. Abstract: Two novel hypoglycemic peptides VY and SFLLR were identified from douchi as the major peptides responsible for the glucose uptake activity. The present work aimed to elucidate their digestion, absorption and transport properties using simulated digestion and Caco-2 cell monolayers transport models. Besides, the effects of digestion and absorption on the structure and activity were also studied. The results showed that VY was resistant to gastrointestinal tract digestion and could cross Caco-2 cell monolayers intactly via both TJs-mediated passive paracellular pathway and PepT1-mediated active route. In comparison, SFLLR was partially degraded into small fragments of SFLL, SFL, and SF by the digestive system, leading to increased glucose uptake activity. Notably, SFLLR, SFLL, and SFL were partly hydrolyzed by aminopeptidase N or dipeptidyl peptidase IV during transport, but they were transported intact. SFL was transported via both paracellular diffusion and PepT1-mediated routes, while SFLLR and SFLL were via paracellular route only.